Implementasi Kampung Tanguh Semeru di Desa Balongmojo Kecamatan Benjeng Kabupaten Gresik - Arini Sulistyowati; Dani Bondan Prakoso (Policy and Maritime Review, 2022)
Semeru tough village is a program and policy that has been issued by the government. This is due to the fact that there are still many people who are confirmed positive for COVID-19 every day. During the implementation of the Semeru tough village, it is hoped that it can reduce the spread of the corona virus so that people are willing to follow the applicable health protocol rules. The purpose of this study is to identify the implementation of Kampung Tangguh Semeru in Desa iBalongmojo iBenjeng Subdistrict iGresik Regency. The type of research used is descriptive qualitative with a case study method or approach. The theory used in the study is the Instruction of the Minister of Home Affairs No. 3 of 2021 which has 3 (three) namely Facilities and Infrastructure, Personnel, and Standard Operating Procedures (SOP). Data collection techniques were carried out by means of in-depth interviews with informants and direct observations. The data analysis techniques used are data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that first, the facilities and infrastructure are adequate enough to run the tough village program, and the condition of the facilities and infrastructure in Balongmojo Village can still be used, and there are no obstacles for these facilities and infrastructure. Semeru in Balongmojo Village because it is assisted by the Village Pustu (village health center), Benjeng sub-district health center, Benjeng police, Benjeng Danramil and Village Linmas, but many people in Balongmojo Village are still not aware of the Semeru Tangguh Village program in Balongmojo Village. Operational Standards The procedure is in accordance with the health protocol and in accordance with the applicable instructions.